Peran Media Audio dalam Meningkatkan Kualitas Proses Pembelajaran Apresiasi Cerita Pendek - Wicaksono, Andi (IAIN Surakarta, 2017)
Learning innovation is an important thing to be possessed by the teacher. This is because through the update that is later success in learning objectives can be delivered optimally. As one of these innovations is the use of learning media. This study was conducted to reveal the effectiveness of the use of audio media in the form of recording readings of short stories on the quality of the learning process of appreciation of the short story. This study used qualitative research methods class action, this study resulted in a conclusion that the audio media can improve the quality of the learning process of short stories with three benchmarks, namely the increasing activity of students during the activity apersepsi, the increased activity of students during the teaching and learning activities, and increased courage students to present the results of its work in the discussion forum.